Rancang Bangun Robot Pemantau Ruangan Menggunakan Jaringan Nirkabel - Cadika Annum Harahap; Muhammad Irawan Manik (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
The development of the robotics world is currently very rapid. This can be proven by the many technologies in the field of robotics that are deliberately created to help human work. This design aims to make Room Control Robot Using Wireless Networks. This room control robot uses two parts, hardware and software. In Hardware use Arduino IDE. In Software using Basic for Android. This research helps users monitor a room by using a robot through applications and wireless media. Users can control the robot by pressing the keyboard or button on the application. As feedback to the user, data recorded by the camera located in the body of the wireless robot will be displayed in the Live View application.